Paradigmas de gestão educacional no contexto do Prêmio Gestão Escolar - Gonçalves, Lilian Fernanda de Melo Bezerra (2020)
This study is part of the research line State Policies and Management of Education, of Programa de Pós-graduação em Educação from Faculdade de Educação of Universidade Federal de Uberlândia (PPGED/FACED/UFU). In the current Brazilian context, in which management principles are inserted in public policies, this master’s dissertation deals with the educational and school management paradigms in the Prêmio Gestão Escolar (PGE). This management award policy is a recognition of Conselho Nacional de Secretários de Educação (CONSED), in relation to schools that present management practices considered effective. The problem that guided the investigation is based on the following question: what management model is described in the PGE and to what extent does the logic of this award lead to a managerial administration? Therefore, the general objective is to analyze the PGE to understand the management model outlined in its documents and prescriptive mechanisms of management in a managerial logic of awards. The specific objectives are: to understand the configuration assumed by the school administration throughout the history of education; to analyze the public management model in the State Reform processes since the 20th century and its effects in the field of educational management; and to analyze conceptions, principles and contradictions present in the PGE. To subsidize the study, we rely on important authors in the field of educational management, both in international level, such as Apple (2005), Ball (2011), Barroso (1996), Dardot and Laval (2011), Havey (2014) and Laval (2019), and in Brazil, like Lima, Shimamoto and Prado (2011), Paro (2012), Pereira (2001), Rosar (2013), Sander (2007), Shiroma (2000), Veiga (1995), among others. The methodological option is based on the qualitative approach, whose data were obtained through documentary research, and we used Content Analysis (CA) as a technique for data treatment and production of inferences. We understand that the PGE, implemented in Brazilian public schools since 1998, has characteristics and contradictions that reveal the principles that defined the new conduct of the State in public policies from the 1990s to the present day and that were guided by neoliberal reforms. Discrepancies are observed in the interface between managerialism and democratic administration, since democratic and managerial principles can be verified in the quality indicators. In this research, we recognized that the PGE and other educational policies and programs are guiding and prescriptive tools for an effective management model to be adopted in public schools which apply to the PGE and that, from a democratic discourse and encouraging collective participation, brings new meanings to autonomy, participation and democratic management. We consider that autonomy assumes the sense of responsibility for the success or failure of educational policies, such as those of external assessment, whose participation sometimes reserves to the school users the position of external evaluators of na acquired service, which makes it possible to benchmark the education institutions. In this sense, the administration appropriates terms supported in democratic management, but it puts its own brand in a context in which neoliberalism has regulated educational policy.